2012
DOI: 10.1016/j.cognition.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Granularity and the acquisition of grammatical gender: How order-of-acquisition affects what gets learned

Abstract: Why do adult language learners typically fail to acquire second languages with native proficiency? Does prior linguistic experience influence the size of the "units" adults attend to in learning, and if so, how does this influence what gets learned? Here, we examine these questions in relation to grammatical gender, which adult learners almost invariably struggle to master. We present a model of learning that predicts that exposure to smaller units (such as nouns) before exposure to larger linguistic units (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
184
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(211 citation statements)
references
References 100 publications
24
184
1
2
Order By: Relevance
“…Indeed, some subcategories in natural languages have partially correlated cues to subcategory structure (e.g., Monaghan et al, 2005), and as described earlier, many investigators have found successful subcategorization learning when distributional cues are correlated with phonological, semantic, or morphological cues (e.g., Gerken et al, 1999; Gerken et al, 2005; Gomez & Lakusta, 2004). Some have also suggested that artificial grammar learning in a semantically-empty world significantly impairs syntax learning (e.g., Moeser & Bregman, 1972; though see Arnon & Ramscar, 2012, for evidence that distributional analyses may be impaired if the learner relies on some types of semantic cues). All of this evidence clearly shows that correlated perceptual cues are relevant for categorization when they are present and that learners can utilize correlated cues to induce categories in experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some subcategories in natural languages have partially correlated cues to subcategory structure (e.g., Monaghan et al, 2005), and as described earlier, many investigators have found successful subcategorization learning when distributional cues are correlated with phonological, semantic, or morphological cues (e.g., Gerken et al, 1999; Gerken et al, 2005; Gomez & Lakusta, 2004). Some have also suggested that artificial grammar learning in a semantically-empty world significantly impairs syntax learning (e.g., Moeser & Bregman, 1972; though see Arnon & Ramscar, 2012, for evidence that distributional analyses may be impaired if the learner relies on some types of semantic cues). All of this evidence clearly shows that correlated perceptual cues are relevant for categorization when they are present and that learners can utilize correlated cues to induce categories in experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity to order allows it to capture the effect of blocking (Kamin, 1969;Rescorla & Wagner, 1972), and to formulate precise predictions about the consequences of order for human learning (Ramscar et al, 2010;Arnon & Ramscar, 2012;Ellis, 2006a).…”
Section: Resultsmentioning
confidence: 99%
“…The blocking phenomenon (Kamin, 1969), for example, explains why an association between a cue and an outcome (the conditioned and unconditioned stimuli in traditional learning theory terminology) is impaired if that same outcome had already been paired with another cue: the second cue will not facilitate prediction of the outcome and for that reason the cue will be ignored. Blocking has been used to explain L2 acquisition (Ellis, 2006a), as well as phenomena of early language acquisition such as overgeneralization of irregular plurals (Ramscar & Yarlett, 2007) and difficulties in acquiring grammatical gender in L2 (Arnon & Ramscar, 2012).…”
Section: Learning Theorymentioning
confidence: 99%
“…As shown by Marsolek (2008), the association strengths between visual features and object names are subject to continuous updating. Ramscar et al (2010) and Arnon and Ramscar (2012) documented the consequences of within-experiment learning in the domain of language. Kleinschmidt and Jaeger (2015) report and model continuous updating in auditory processing in the context of speakerlistener adaptation.…”
Section: Introductionmentioning
confidence: 99%